Bilingualism and the severity of poststroke aphasia. Issue 1 (2nd January 2019) - Paplikar, Avanthi; Mekala, Shailaja; Bak, Thomas H.; Dharamkar, Santosh; Alladi, Suvarna; Kaul, Subhash
ABSTRACT: Background : Bilingualism has been associated with cognitive benefits in healthy people as well as in patients with cognitive impairment due to stroke and dementia. However, the relationship between bilingualism and aphasia is more complex. While bilinguals are as likely as monolinguals to develop aphasia after stroke, studies of relationship between bilingualism and severity of poststroke language recovery are few and have produced conflicting results, with much evidence derived from immigrant populations or small case series. Aims : Against this background of limited number of studies, we set out to explore the relationship between bilingualism and severity of language impairment in stroke aphasia. We explored the hypothesis that enhanced cognitive abilities related to bilingualism may have a positive impact on recovery from aphasia. Methods & Procedures : We investigated 38 bilingual and 27 monolingual patients who participated in a longitudinal hospital-based stroke registry and were evaluated at least 3 months after stroke (mean 11.5 months). Patient performance on language and other cognitive functions was evaluated with Addenbrooke's Cognitive Examination – Revised (ACE-R) validated for use in aphasia in local languages and for varying educational levels. The results of monolinguals and bilinguals were compared after accounting for confounding variables, including age, gender, education, occupation, medical, and stroke characteristics. Outcomes & Results : Aphasia severity as measured by the language domain sub-scores (total of language and fluency scores) of ACE-R was significantly higher in monolinguals compared with bilinguals (7.0 vs. 14.4, maximum score 40; p = 0.008, effect size = −0.691). Bilinguals performed significantly better than their monolingual counterparts in attention, memory, and visuospatial domains of ACE-R. A univariate general linear model analysis showed that bilingualism was significantly associated with higher language domain scores of ACE-R after adjusting for other confounding variables. Conclusions : The results suggest that although bilingual speakers are at equal risk of developing aphasia after stroke as monolingual ones, their aphasia is likely to be less severe.